Modulated theta band frequency with binaural beat stimulation correlates with improved cognitive scores in Alzheimer’s patients - Mujib, Muhammad Danish; Rao, Ahmad Zahid; Haque, Muhammad Fahim Ul; Alokaily, Ahmad O.; Hussain, Syeda Sehar; Aldohbayb, Ahmed A.; Qazi, Saad Ahmed; Hasan, Muhammad Abul (Frontiers in Aging Neuroscience, 2025)
IntroductionAlzheimer’s disease (AD) affects 50 million individuals worldwide, a number projected to triple by 2050. Due to discomfort through electrical and magnetic neuromodulation technologies, this is the first study to propose the potential of auditory binaural beat (BB) stimulation at an alpha frequency (10 Hz) for enhancing cognitive and neurological outcomes in AD patients.MethodsTwenty-five patients were divided into the experimental-Group (n = 15) and control-Group (n = 10). Psychometric and neurological assessments were conducted Pre-Treatment (Day 1) and Post-Treatment (Day 14) following consecutive days of binaural beats (BB) or auditory tone stimulation administered from Day 2 to Day 13.ResultsA two-way ANOVA revealed a significant main effect of group (F = 6.087, p = 0.016) and session (F = 3.859, p = 0.024) on MMSE scores, with the experimental group showing significant improvement in MMSE scores (t = 7.33, p = 0.00000012) compared to the control group (p = 0.2306). Paired t-tests revealed a significant reduction in depression scores (DASS-21, t = 1.701, p = 0.0253) in the experimental group, while no significant improvements were noted in the control group. EEG recordings revealed significant changes in α-band, β-band, and γ-band power (p < 0.05). Moreover, The correlation between EEG bands and MMSE subparts showed that increased θ-band power in the experimental group was positively correlated (p < 0.05) with the frontal region during language tasks and in the frontal and central regions during registration and orientation tasks, indicating potential neurocognitive benefits.DiscussionThe results of this research imply that BB stimulation has untapped potential as a non-invasive therapy for patients with AD, hence there is the need for further studies to manage the dementia epidemic.